Breaking the Mold: Male Jewelry Branding, Consumer Behavior, and SDG Pathways in Lebanon’s Luxury Market - Khoury, Josiane El (Journal of Cultural Analysis and Social Change, 2025)
This article examines a recent branding disruption in the luxury jewelry sector: a new entrant that deliberately does not compete on women’s collections and instead positions itself as the largest men’s collection in the market. Framed through branding and consumer-culture theory, the study analyzes how this male-centric positioning challenges category conventions historically feminized in jewelry, and how it reconfigures the semiotics of luxury, identity, and status. These dynamics are mapped to relevant Sustainable Development Goals (SDGs), notably SDG 5 (Gender Equality), SDG 10 (Reduced Inequalities), and SDG 12 (Responsible Consumption and Production), arguing that inclusive product architectures can expand representation while reshaping demand signals and consumption rituals. Methodologically, this qualitative inquiry employs brand communication and social media analysis to trace meaning transfer, emotional branding, and archetype construction. Findings suggest that category leadership claims—such as “largest men’s collection”—can legitimize new consumption scripts, normalize male jewelry as identity work, and foster more equitable brand storytelling. The study concludes with implications for market shaping, influencer collaboration, and sustainable brand development strategies aligned with SDGs.